Comparative pharmacokinetics of gastrodin in rats after intragastric administration of free gastrodin, parishin and Gastrodia elata extract. (24th December 2015) - Tang, Chunlan; Wang, Li; Liu, Xinxin; Cheng, Mengchun; Qu, Yang; Xiao, Hongbin
Abstract: Ethnopharmacological relevance: Gastrodia elata Blume, a traditional Chinese herb, was widely used against convulsant, vertigo, paralysis, epilepsy, tetanus, asthma and immune dysfunctions. Gastrodin is one of the major bioactive components of G. elata and it is known for its anticonvulsive, anti-inflammatory, antiepileptic and neuroprotective effects. Materials and methods: An ultra high performance liquid chromatography-fluorescence detection (UHPLC-FLD) method was developed to determine gastrodin in rat plasma. Gastrodin and Thiamphenicol (internal standard, IS) were extracted from rat plasma by immediately protein precipitation. The pharmacokinetics of gastrodin in rats by following differently administered types was studies: intragastric administration of gastrodin (100 mg/kg), parishin (116 mg/kg, with the same mole of gastrodin moiety) and G. elata extract (2.3 g/kg, with the same mole of gastrodin moiety). Non-compartmental pharmacokinetic profiles were constructed using the software of WinNonlin (Phoenix, version 6.3), and the pharmacokinetic parameters were compared using unpaired Student's t -test. Results: The results showed that the pharmacokinetic parameters, including C max, T max, AUC0–∞, t 1/2, MRT, V d, CL, were quite different among the three types of gastrodin administration. The administration of parishin and G. elata extract, which either could convert to gastrodin in vivo or contained free gastrodin and abundant gastrodin conjugates, gave rise to higher elimination half-life ( t 1/2 ) and mean residence time (MRT) values for gastrodin compared to free gastrodin administered. Conclusion: The comparison of the pharmacokinetics of gastrodin among three different administered types of gastrodin in rats suggested that administration of parishin or G. elata extract in clinic may result in a longer duration time of action than that of the administration of free gastrodin. The results may provide some guidance for the clinical applications of parishin and G. elata . Graphical abstract: